Comparison of different heat integration pressure swing distillation processes for separating isobutanol and p-xylene azeotrope - Shisheng Liang; Guangle Bu (Scientific Reports)
Abstract Chemical process intensification has attracted extensive interest of scholars. Distillation, as a high energy consumption industry, is in urgent need of energy saving and CO2 emissions reduction by means of process intensification. In this paper, isobutanol and p-xylene azeotrope was separated by pressure swing distillation (PSD). Combined with process integration method, four heat integration PSD processes including partial heat integration PSD (PHI-PSD), enhanced partial heat integration PSD (EPHI-PSD), full heat integration PSD (FHI-PSD), and enhanced full heat integration PSD (EFHI-PSD) were designed and optimized through sequential iterative procedure. The total annual cost (TAC), CO2 emissions, and thermodynamic efficiency were calculated and compared. By comparing relevant data, it is found that EPHI-PSD process has obvious advantages in terms of economic, thermodynamic efficiency, and environmental benefits. Specifically, comparing with the basic PSD process, thermodynamic efficiency of EPHI-PSD process is improved by 97.8% while TAC and CO2 emissions are decreased by 37.0% and 50.1%, respectively.